Perancangan Hotel Bintang Empat di Kota Tarakan Kalimantan Utara Dengan Pendekatan Arsitektur Neo Vernakular - Rizaldi Bilhaq Firdaus; Widi Cahya Yudhanta2 (Mutiara : Jurnal Penelitian dan Karya Ilmiah, 2025)
Tarakan City, with its enormous potential as a center for economic, trade, and tourism, faces challenges in providing premium accommodation facilities. Although the city continues to grow rapidly, particularly with the growth of the tourism sector driven by its natural beauty and cultural diversity, the availability of adequate four-star hotels remains limited. This poses a barrier to the growth of domestic and international tourists who require comfortable and quality accommodation facilities. Therefore, the design of this four-star hotel is crucial to strengthening Tarakan City's tourism sector, which can not only provide quality accommodation but also have a positive impact on the local economy. The application of the Neo-Vernacular Architecture concept in the design of this hotel aims to connect the past with the future, by combining local traditional elements that are characteristic of Tarakan's culture, such as the Baloy Mayo traditional house, with the functional and modern requirements required for a four-star hotel development. This approach is expected to create a building that not only meets international standards of comfort and facilities, but also has a strong identity, reflects the richness of local culture, and provides high aesthetic value. In this design, the tropical climate of Tarakan City is also a major consideration, so that the hotel building is not only comfortable, but also environmentally friendly and can optimize the use of natural energy. Thus, this hotel is expected to function not only as a place to stay, but also as a symbol of tourism progress that still maintains cultural and environmental sustainability. The design of this four-star hotel also pays attention to aspects of sustainability and environmental friendliness, which are now essential requirements in every modern architectural project.